Influence of rapidly successive head impacts on brain strain in the vicinity of bridging veins. (5th July 2017) - Knowles, Brooklynn M.; MacGillivray, Samantha R.; Newman, James A.; Dennison, Christopher R.
Abstract: Acute subdural hematoma due to a bridging vein rupture is a devastating but rare injury. There has to date been no satisfactory biomechanical explanation for this infrequent but costly injury. We surmise that it may be associated with multiple head impacts. Though numerical models have been used to estimate vein strains in single impact events, none to date have examined the influence on localized brain strain of rapidly consecutive impacts. Using the Simulated Injury Monitor, we investigated the hypothesis that such double impacts can increase strain beyond that created by any single impact. Input to our parametric study comprised hypothetical biphasic rotational head accelerations producing a maximum angular velocity of 40 rad./s. In each of 19 simulations, two identical angular inputs are applied at right angles to each other but with time separations varying from 0 to 40 ms. For these double impacts, it has been generally found that strain in the region of the bridging veins is different, than what would be associated with any corresponding single impact. In some cases, the effect is to actually reduce the tissue strain. In others, the strain in the region of the bridging veins is increased markedly. The mechanistic explanation for the strain increase is that the tissue strain from the first impact has not diminished fully when strain from the second impact is initiated. Rapidly consecutive impacts could be a potential mechanism leading to vein rupture that warrants further investigation.